Letter (copy) : Refugees in France - Citrine, Walter, 1887-1983
027-0032-001 INTERNATIONAL. WMC/WJB/NS/65. 19th March, 1940. Mrs. Ruth Fasnacht, Organizing Secretary, Oxford City Labour Party, 4c Park End Street, Oxford. Dear Madam, REFUGEES IN FRANCE. We have received your letter containing a copy of your resolution with regard to the position of refugees in France. This shall have our attention. Yours faithfully, General Secretary. 292/946/27/32